The role of uncertainties in the design of international water treaties: an historical perspective - Drieschova, Alena; Fischhendler, I.; Giordano, Mark (Springer, 2011)
Water is one natural resource whose management is especially susceptible to uncertainties, many of which are being exasperated by climate change. Some of these uncertainties originate from knowledge deficits in physical conditions while others relate to behavioral and social variability related to water supply and use. However, to our knowledge no quantitative analysis of how uncertainties have been translated into transboundary water treaty structures exists. The present paper partially fills this gap through an examination of how uncertainty has been reflected in basin specific transboundary treaties and how that reflection has changed over the last century. While we could identify only minor trends in the frequency with which uncertainties are mentioned in treaties, we did find two clear patterns in the strategies adopted to deal with them. First, treaties seem to adopt a portfolio approach that spreads the dangers of uncertainty by concurrently including several management strategies simultaneously. Second, there is a trend towards more openended strategies in recent decades, rather than hard codification of rules as had earlier been more common.